Driving against the clock: Investigating the impacts of time pressure on taxi and non-professional drivers’ safety and compliance - Qinaat Hussain (15294164) (2024)
Drivers often encounter time pressure, which can lead to riskier driving habits, decreased safety margins, and a higher chance of accidents. Given that taxi drivers frequently experience these conditions, this study examines how time pressure impacts the driving behaviors of both taxi and non-professional drivers. In this regard, a driving simulator experiment was carried out to assess the driving behaviors of both groups under time pressure. The simulation drive included different scenarios such as a stop sign, a pedestrian crosswalk, four intersections, a school zone, a slow bus and a drop-off location. The study recruited 55 taxi drivers and 55 non-professional drivers to take part in the experiment. Each participant completed the simulation drive twice, with the second drive conducted after they were informed that a reward would be given for finishing the trip more quickly. The findings reveal that drivers exhibited significantly riskier behaviors under time pressure, including higher speeds and reduced adherence to traffic rules. When comparing both groups, non-professional drivers displayed higher speeds and riskier behaviors across various scenarios, whereas taxi drivers were more likely to commit violations associated with drop-offs. These findings call for targeted awareness campaigns and stricter enforcement to reduce risky behaviors under time pressure. Flexible scheduling for non-professional drivers and incentive programs for taxi drivers can further promote safer practices. Policymakers can use these insights to design strategies that address the risks associated with time pressure. Other Information Published in: Accident Analysis & Prevention License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.aap.2024.107864